Resolving Partnership Ambivalence: A Randomized Controlled Trial of Very Brief Cognitive and Experiential Interventions with Follow-Up - Trachsel, Manuel; Ferrari, Lara; Grosse Holtforth, Martin (Canadian Journal of Counselling and Psychotherapy, 2012)
Both the experiential two-chair approach (TCA) and the cognitive decision-cube technique (DCT) have been used for the treatment of ambivalence in counselling. The aims of this study were (a) to show that partnership ambivalence is reduced after a brief stand-alone intervention using either TCA or DCT, and (b) to test the hypothesized mechanisms of change processual activation and clarification. Fifty ambivalent participants were randomly assigned to either TCA or DCT interventions of two sessions each. Results indicated that partnership ambivalence was reduced after both interventions. The TCA was associated with a significantly higher processual activation than was the DCT.